2012
DOI: 10.1158/0008-5472.can-11-3832
|View full text |Cite
|
Sign up to set email alerts
|

DEDD Interacts with PI3KC3 to Activate Autophagy and Attenuate Epithelial–Mesenchymal Transition in Human Breast Cancer

Abstract: Epithelial-to-mesenchymal transition (EMT), a crucial developmental program, contributes to cancer invasion and metastasis. In this study, we show that death-effector domain-containing DNA-binding protein (DEDD) attenuates EMT and acts as an endogenous suppressor of tumor growth and metastasis. We found that expression levels of DEDD were conversely correlated with poor prognosis in patients with breast and colon cancer. Both in vitro and in vivo, overexpression of DEDD attenuated the invasive phenotype of hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 48 publications
5
120
0
Order By: Relevance
“…Several reports demonstrated that autophagy was involved in the EMT progress of some cell lines or tumor tissues, [39][40][41][42] and the embryonic EMT was similar to the transformation of cell phenotype during carcinoma progression. 43 Thus, we did perform the evaluation of E-Cadherin, N-Cadherin and laminin expression following the treatment of RAPA and 3-MA (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrated that autophagy was involved in the EMT progress of some cell lines or tumor tissues, [39][40][41][42] and the embryonic EMT was similar to the transformation of cell phenotype during carcinoma progression. 43 Thus, we did perform the evaluation of E-Cadherin, N-Cadherin and laminin expression following the treatment of RAPA and 3-MA (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…5,29 Transient transfection was performed using Lipofectamine2000 (Invitrogen, 11668019) according to the manufacturer's instructions. To generate MDA-MB-231 cells stably expressing the pCMV6-AN-MYC and the MYCtagged SLC9A3R1 plasmids were both transfected into MDA-MB-231 cells.…”
Section: Reagentsmentioning
confidence: 99%
“…To generate MDA-MB-231 cells stably expressing the pCMV6-AN-MYC and the MYCtagged SLC9A3R1 plasmids were both transfected into MDA-MB-231 cells. After 24 h of transfection, stable transfectants were selected using neomycin (Invitrogen, 10131035), 5 and a single clone was amplified using a dilution cloning technique. To generate MCF-7 cells stably expressing the controlshRNA and SLC9A3R1-shRNA plasmids were both transfected into MCF-7 cells.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently demonstrated that ectopic expression of the DEDD gene in the MDA-MB-231 metastatic breast cancer cell line led to the degradation of the EMT inducers Snail and Twist through autophagy activation (30). Reversely, knockdown of DEDD in the MCF7 non-metastatic breast cancer cell line led to autophagy reduction and EMT promotion (30).…”
Section: Role Of Autophagy In Cancermentioning
confidence: 99%